Comparative analysis of open green spaces policies in enhancing urban resilience to climate change through small urban parks in Malaysia and Singapore - Mohammad Sabri, Siti Afiqah; Ponrahono, Zakiah; Abu Bakar, Aisyah; Abdul Aziz, Fatiah (Italian Association of Chemical Engineering, 2023)
This comparative analysis investigates the effectiveness of open green spaces policies in promoting urban resilience to climate change in the context of dense cities in Malaysia and Singapore. With rapid urbanisation and increasing population density, managing the impacts of climate change is crucial for sustainable urban development. Small urban parks (SUPs) have emerged as valuable assets in enhancing urban resilience and mitigating climate-related risks. This study draws on a comprehensive review of secondary sources, including government reports and academic literature, to compare the strategies employed in both countries' open green spaces policies. The analysis examines the similarities and differences in policy frameworks, regulations, and management approaches. The study reveals that while both Malaysia and Singapore recognise the importance of open green spaces in addressing climate change impacts, there are variations in the specific policies and approaches adopted. The findings contribute to the existing body of knowledge on open green space policies in dense cities and offer valuable recommendations for policymakers and urban planners in Malaysia, Singapore, and beyond. Overall, this study highlights the significance of effective open green spaces policies in fostering urban resilience to climate change and calls for further research and collaboration in this important area.